The state of the science of interprofessional collaborative practice: A scoping review of the patient health-related outcomes based literature published between 2010 and 2018. - May Nawal Lutfiyya; Linda Feng Chang; Cynthia McGrath; Clark Dana; Martin S Lipsky (PLoS ONE)
Introduction If interprofessional collaborative practice is to be an important component of healthcare reform, then an evidentiary base connecting interprofessional education to interprofessional practice with significantly improved health and healthcare outcomes is an unconditional necessity. This study is a scoping review of the current peer reviewed literature linking interprofessional collaborative care and interprofessional collaborative practice to clearly identified healthcare and/or patient health-related outcomes. The research question for this review was: What does the evidence from the past decade reveal about the impact of Interprofessional collaborative practice on patient-related outcomes in the US healthcare system? Materials and methods A modified preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach was followed. Results Of an initial 375 articles retrieved 20 met review criteria. The most common professions represented in the studies reviewed were physicians, pharmacists and nurses. Primary care was the most common care delivery setting and measures related to chronic disease the most commonly measured outcomes. No study identified negative impacts of interprofessional collaborative practice. Eight outcome categories emerged from a content analysis of the findings of the reviewed studies. Conclusions The results suggest a need for more research on the measurable impact of interprofessional collaborative practice and/or care on patient health-related outcomes to further document its benefits and to explore the models, systems and nature of collaborations that best improve population health, increase patient satisfaction, and reduce cost of care.